Starting Torque Pulsation of Single-phase Asynchronous Motors - Katkevičius, V.; Gečys, S.; Kalvaitis, A.; Rinkevičius, G. (Elektronika ir Elektrotechnika, 2003)
The starting torque pulsations of asynchronous motors are the change of the magnitude of starting torque depending on the angle of rotor rotation with respect to the standing stators coordinates. The synchronous torques are the main reason of the starting torque pulsation. The occurring conditions of the synchronous torques of the single-phase asynchronous motors at the starting conditions are analyzed. The like stator harmonics and rotor harmonics according to the direction of rotation however in spite of what creates these ones and did not induced each other created the synchronous torques at the starting conditions of motor. The curves of stating torque pulsations of the investigated electrical motors were recorded with the created measuring device of pulsating torque [7]. The stating torque pulsations of the salient – pole single – phase asynchronous motors may be decreased by choosing the geometry of the stator poles and the air gap and the odd number of rotor slots. Ill. 3, bibl. 7 (in Lithuanian; summaries in Lithuanian, English, Russian).